Mangroves on Two Islands: Ecological Study in Java and South Tapanuli - Hendarto, Totok (Assyfa Journal Scientific Essay, 2023)
This research explores the ecology of mangroves on two islands, Java and South Tapanuli, using a systematic literature review (SLR) approach based on data from Scopus for the last three years. This research aims to assess the characteristics of the mangrove ecosystem in these two regions and understand the factors that influence the ecological sustainability of mangroves. This research used strict inclusion criteria, involved relevant and peer-reviewed scientific articles, and included several studies that focused on mangrove waters' physical, chemical, and biological aspects. The research results show significant differences in the characteristics of mangrove waters between Java and South Tapanuli. In Java, mangroves tend to have higher densities. It includes more stable water conditions, while in South Tapanuli, mangroves are more fragmented with higher variability in water conditions. In addition, this research reveals areas for improvement in mangrove management and conservation in both regions, including a need for more supportive policies and minimal community participation in conservation efforts. This research also suggests the need for improvements in mangrove ecosystem management through community-based approaches and more integrated policies. Significant increases in community participation and more effective policy implementation are needed to continue healthy and sustainable mangrove ecosystems. This research provides important insights for policymakers, researchers, and conservation practitioners in mangrove conservation efforts in Indonesia.